A rare case report on atypical odontalgia with psychological implications - Divya Pandya; Anil Kumar Nagarajappa (International Journal of Medical Research and Review, 2016)
Psychosomatic or somatoform disorders are among the most common psychiatric disorders found in general practice. A psychosomatic disorder involves both body and mind. These diseases have physical symptoms originating from mental or emotional causes. Most common ones are stress, anxiety and depression. A wide spectrum of psychiatric disorders may influence the orofacial region, where unfortunately they remain unrecognized due to limited nature of their presenting features. We here present a case report of atypical odontalgia in an elderly male secondary to underlying psychological distress.